2002
DOI: 10.1046/j.1440-1843.2002.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating levels of soluble Fas ligand are correlated with disease activity in patients with fibrosing lung diseases

Abstract: Although further studies need to be performed on a large number of patients with histologically proven IPF or CVD-IP, it would seem that serum sFasL levels may reflect the activity of IPF and CVD-IP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 28 publications
3
33
0
1
Order By: Relevance
“…The death receptor Fas was found to be expressed in AECs within the lungs of IPF patients and circulating levels of its ligand FasL correlated with disease activity. [40][41][42] Similar observations were observed in animal models. 43,44 Activation of Fas-induced apoptosis of bronchial and AECs is sufficient to initiate a fibrotic response in animal models.…”
supporting
confidence: 70%
“…The death receptor Fas was found to be expressed in AECs within the lungs of IPF patients and circulating levels of its ligand FasL correlated with disease activity. [40][41][42] Similar observations were observed in animal models. 43,44 Activation of Fas-induced apoptosis of bronchial and AECs is sufficient to initiate a fibrotic response in animal models.…”
supporting
confidence: 70%
“…TGF-b 1 is believed to play an important role in this dysregulation because it is expressed in an exaggerated fashion in IPF where, in contrast to controls, a sizable percentage of this cytokine is biologically active (45)(46)(47). In fact, the apposition of apoptosis, fibrosis, and the exaggerated expression of TGF-b 1 are well documented in IPF (48)(49)(50)(51). TGF-b 1 is also a critical mediator of the pulmonary fibrosis that is seen after bleomycin administration, a commonly used animal model of IPF (5,52).…”
Section: Discussionmentioning
confidence: 99%
“…with a NSIP. Kuwano et al reported increased KL-6 levels in IPF patients with signs of disease progression in the previous three months, compared to stable IPF patients [32]. Again, as this study was performed prior to 2002, one should bear in mind that the diagnosis of IPF was since then reclassified [1].…”
Section: Kl-6mentioning
confidence: 99%